You have not given the data for which you like to find the median.
I will however explain how you can find the median of a given set of data, and you can apply the same method to your problem.
Step-by-step explanation:
Median, just like it sounds, is simply the middle value of a given set of data.
Given a set of numbers:
a, b, c, d, e, ..., z.
To find the median, first,
- Arrange the numbers a, b, c, d, e, ..., ..., z in an ascending or descending order.
- Count the whole numbers, if it is odd, you have a middle number, and that is the median.
If it is even, you have two middle numbers, then the median will be the addition of those two numbers divided by two.
Example: To find the median of
4, 5, 2, 1, 2, 6, 7, 3, 5.
First, we arrange in ascending:
1, 2, 2, 3, 4, 5, 5, 6, 7
Next, we locate the middle number(s), which is 4.
The MEDIAN is 4 .
Example 2: To find the median of
9, 4, 5, 2, 1, 2, 6, 7, 3, 5.
First, we arrange in ascending:
1, 2, 2, 3, 4, 5, 5, 6, 7, 9
Next, we locate the middle number(2), which are 4 and 5.
The median = (4 + 5)/2
= 9/2
= 4.5
The MEDIAN is 4.5.
Suppose you want to fly for a party. Three rolls of streamers and 15 party hats cost $30. Larry, you've got two rolls of streamers in for a party hats for $11. How much did each role of streamers cost? How much did each party hat cost? Suppose you want to fly for a party. Three rolls of streamers and 15 party hats cost $30. Where, you bought two rolls of streamers and four party hats for $11. How much did each role of streamers cost? How much did each party hat cost?
Answer:
Each steamer costs $2.5 and each party hat costs $1.5
Step-by-step explanation:
Let the cost of 1 steamer =x
Let the cost of 1 party hat =y
Three rolls of streamers and 15 party hats cost $30
3x+15y=30Two rolls of streamers and four party hats for $11.
2x+4y=11We solve the two equations simultaneously.
Multiply equation 1 by 2 and equation 2 by 3
6x+30y=60
6x+12y=33
Suntract
18y=27
y=1.5
From 6x+30y=60
6x+30(1.5)=60
6x+45=60
6x=60-45=15
x=2.5
Since x=2.5 and y=1.5
Each steamer costs $2.5 and each party hat costs $1.5
Answer:
each role of streamers cost $2.5
each party hat cost $1.50
Step-by-step explanation:
Let 's' represent rolls of streamers and 'h' represent party hats
Lets form an equation first
=>For three rolls of streamers and 15 party hats cost $30.
3s + 15h = 30
s= (30-15h)/3 ----> eq(1)
=>For 2 rolls of streamers and 4 party hats cost $11.
2s + 4h = 11
s= (11 -4h)/2 ----> eq(2)
Lets equate eq 1 and 2 in order to find 'h'
(30-15h)/3= (11 -4h)/2 ---->(applying cross multiplication)
60 - 30h = 33 - 12h
60-33 = 30h -12h
27 = 18 h
h= 27/18 => 1.50
therefore, each party hat cost $1.50
substitute above value in eq 1
(1)=> s= (30-15h)/3
s= 30-(15 x 1.5) / 3
s= 2.5
Therefore, each role of streamers cost $2.5
Which is the solution to the system of equations:
x + y = -7
3x + 2y = -17
O (-1,-6)
O (3, -13)
O (4, -11)
O (-3,-4)
Answer:
HOW IS THIS HIGH SCHOOL?! ITS SO EASY ITS D
Step-by-step explanation:
Answer:
The fourth one
Step-by-step explanation:
if you plug the values in then you would get
(-3) + (-4) = -7
3(-3) + 2(-4) = -17
-7 = -7
-8 + -9 = -17
-17 = -17
True
To prove part of the triangle midsegment theorem using
the diagram, which statement must be shown?
O
The length of JK equals the length of JL.
The length of GH is half the length of KL.
The slope of JK equals the slope of JL.
The slope of GH is half the slope of KL.
The statement that must be shown to prove part of the triangle midsegment theorem is: B. The length of GH is half the length of KL
What is the Midsegment Theorem?The Midsegment Theorem of a triangle states that the length of the midsegment (line segment joining two sides of a triangle) is half the length of the third side (the base) of the triangle.Midsegment = ½(third side/base)Given ΔJKL with a midsegment of GH as shown in the diagram attached below:
GH is the midsegment
KL is the base (third side)
Therefore, the statement that must be shown to prove part of the triangle midsegment theorem is: B. The length of GH is half the length of KL
Learn more about the midsegment theorem on:
https://brainly.com/question/8370301
INVESTING Maria invests $1000 in a savings account that pays 4% interest compounded annually. The value of the account A at the end of five years can be determined from the equation log10 A = log10[1000(1 + 0.04)5]. Write this equation in exponential form
Answer:
[tex]A=1000(1+0.04)^5[/tex]
Step-by-step explanation:
-The general expression of an exponential function is :
[tex]A=P(1+r)^n[/tex]
where:
[tex]A[/tex] is the amount after time t.[tex]P[/tex] is the initial amount[tex]r[/tex] is the rate of growth[tex]t[/tex] is the time.We substitute our parameter values in the equation as:
[tex]A=1000(1+0.04)^5[/tex]
Final answer:
To write the given equation in exponential form, raise the base value of 1000 to the power of (1 + 0.04)⁵.
Explanation:
To write the given equation in exponential form:
Start with the base value, in this case, 1000.
Raise the base to the power of the exponent, which is (1 + 0.04)⁵.
The exponential form would be 1000 * (1 + 0.04)⁵.
Which of the following phrases are equations?
Choose 2 answers:
© b = 9
© 7+ 19 = 26
© a +9 > 72
©
X
+Y-
Colo
Answer:
d
Step-by-step explanation:
The two phrases that are equations are 'b = 9' and '7 + 19 = 26' because both have an equals sign, indicating that two expressions are set equal to each other.
An equation is a mathematical statement that asserts the equality of two expressions, and it is characterized by the presence of an equals sign '='. From the given options, the two phrases that qualify as equations are b = 9 and 7 + 19 = 26. These both show a relationship where two expressions are set equal to each other.
The phrase a +9 > 72 is not an equation, but an inequality because it uses a greater than symbol '>' instead of an equals sign. The last option provided seems to be typos or irrelevant content and does not constitute an equation.
Determine the surface area of the triangular prism below
A. 2,001
B. 2,376
C. 2,592
D. 4,320
Answer:
2376 square feet
Step-by-step explanation:
40 x 15 = 600
40 x 24 = 960
1/2 x (24 x 9) = 108
600 + 600 + 960 + 108 + 108 = 2376
To find the average or mean of a set of numbers, add up all the items and divide by…?
Answer: divide it by the number of numbers you added up.
Step-by-step explanation:
For example, let's say you had to find the average of 1, 2, and 3. You add all the numbers up to get 6. Since you had to add 3 numbers together (1, 2, 3) to get 6, you divide 6 by 3 to get the mean/average, which in this case, is 2
To find the average or mean of a set of numbers, add up all the items and divide by how many numbers there are.
How do you find the average set of numbers that add up all the items and divide by?The mean is the average of the numbers. It is easy to calculate: add up all the numbers, then divide by how many numbers there are. In other words, it is the sum divided by the count.
How do you find the mean in a set of numbers?The mean, or average, is calculated by adding up the scores and dividing the total by the number of scores.
Learn more about average here https://brainly.com/question/6504879
#SPJ2
what is the answer to log100
Answer:
the answer is 2
Step-by-step explanation:
Answer:
2
Step-by-step explanation:
find the slope of the line (-3,-3) (1,1)
Answer: The slope is m = 1
Step-by-step explanation:
-To find the slope, you need the slope formula:
[tex]m=\frac{y2-y1}{x2-x1}[/tex] where you have [tex](x1,y1)[/tex] and [tex](x2,y2)[/tex] on the equation.
-Next, you put the two points to the equation:
[tex]m=\frac{1+3}{1+3}[/tex]
-And then you solve the equation:
[tex]m=\frac{1+3}{1+3}[/tex]
[tex]m=\frac{1+3}{1+3} = \frac{4}{4}=1[/tex]
[tex]m=1[/tex]
The slope of line having (-3,-3) (1,1) as points is 1 .
Given,
Points: (-3,-3) (1,1)
To find the slope, you need the slope formula:
m = y2 -y1 /x2 - x1
Here,
(x1 , y1 ) = (-3,-3)
(x2 , y2) = (1,1)
So,
Substitute the values in slope formula ,
m = y2 -y1 /x2 - x1
m = 1 - (-3)/1 - (-3)
m = 4/4
m = 1
Thus the slope of line is 1 .
Know more about slope of line,
https://brainly.com/question/14511992
#SPJ2
Find the center and the radius of the circle given the equation of a circle
below.
(x - 2)^2 + (y – 5)^2 = 49
A: Center: (2,5) & Radius=7
B: Center: (5,2) & Radius=49
C: Center: (-2,-5) & Radius=49
D: Center: (-5,-2) & Radius= 7
Option A) Center: (2,5) & Radius=7 is the correct one.
Step-by-step explanation:
The general form of the equation of the circle is given as :
⇒ (x-h)² + (y-k)² = r²
where,
(h, k) are coordinates of the center point of the circle.r is the radius of the circle.Therefore, you need to compare the given equation with the general equation of the circle.
The given equation of circle is (x-2)² + (y-5)² = 49
From the given equation, it can be determined that
h = 2 and y = 5 and r² = 49
The center (h,k) of the circle is (2,5).
To find the radius r :
⇒ r² = 49
⇒ r = 7
The radius of the circle is 7.
∴ Option A) Center: (2,5) & Radius=7 is the correct one.
Mike claims that (2^3)^5= 2^15. Sarah claims that (2^3)^5= 2^8. Who is correct? Explain your reasoning.
Mike is correct, because the rules for powers and exponentiation say that when you elevate a certain base which is already being elevated to a certain power, the powers multiply.
This means that:
[tex] {( {a}^{b} )}^{c} = {a}^{bc} [/tex]
Or, using your example:
[tex] {( {2}^{3} )}^{5} = {2}^{3 \times 5 } = {2}^{15} [/tex]
what is the volume in cubic ft of a rectangular prism with a height of 17ft a width of 13 ft and a length of 12ft
Answer:
The answer is 2652 ft^3 (cubed)
Step-by-step explanation:
To find the volume of a rectangular prism, you need to multiply base X height or Bh.
1. Multiply length by width12 X 13 = 156 ft^2 (squared)2. Multiply base by height156 ft (squared) X 17 ft = 2652 ft^3 (cubed)Answer:2654
Step-by-step explanation:
if m∠XAB = 32, what is m∠BAC?
A.) 16
B.) 58
C.) 64
D.) 32
Answer:
the answer is c
Step-by-step explanation:
the picture in the attached figure
we know that
The construction shown is an angle bisector
m<XAB=m<CAX
so
m<BAC=2*[m<XAB]-----> 2*32°----->m<BAC= 64°
Simplify this equation p+p+3 = 13*
O 2+p+ 2 = 13
O 2p+ 3 = 13
O
2p = 10
Answer:
P=3 hope this helps! Sorry if I get it wrong. Hope I get brainliest! :D
Step-by-step explanation:
Simplifying
3p + -1 = 5(p + -1) + -2(7 + -2p)
-1 + 3p = 5(p + -1) + -2(7 + -2p)
-1 + 3p = 5(-1 + p) + -2(7 + -2p)
-1 + 3p = (-1 * 5 + p * 5) + -2(7 + -2p)
-1 + 3p = (-5 + 5p) + -2(7 + -2p)
-1 + 3p = -5 + 5p + (7 * -2 + -2p * -2)
-1 + 3p = -5 + 5p + (-14 + 4p)
-1 + 3p = -5 + -14 + 5p + 4p
-5 + -14 = -19
-1 + 3p = -19 + 5p + 4p-1 + 3p = -19 + 9p
Solving
-1 + 3p = -19 + 9p
Solving for variable 'p'.
Move all terms containing p to the left, all other terms to the right.
Add '-9p' to each side of the equation.
-1 + 3p + -9p = -19 + 9p + -9p
Combine like terms: 3p + -9p = -6p
-1 + -6p = -19 + 9p + -9p
Combine like terms: 9p + -9p = 0
-1 + -6p = -19 + 0
-1 + -6p = -19
Add '1' to each side of the equation.
-1 + 1 + -6p = -19 + 1
Combine like terms: -1 + 1 = 0
0 + -6p = -19 + 1
-6p = -19 + 1
Combine like terms: -19 + 1 = -18
-6p = -18
Divide each side by '-6'.
p = 3
Simplifying
p = 3
(25 points) Find the probability that a randomly selected student drives to school.
Answer:
2/5
Step-by-step explanation:
40 students drive to school
40/100 drive to school
2/5
Step-by-step explanation:
Hello there!
Add all of the values in the table to get the total amount of students.
25+25+20+13+5+5+3+2+2=(70)+(23)+(4)=97
Then, make your probability:
P(Drive to school)=(How many students drive)/(All students)
P=40/97
;)
I have to give the answer in by 8pm
Answer:
15
Step-by-step explanation:
TV = TU+UV
= 12 + 3
TV = 15
Find the value of x
46.
92.
78.
98.
Answer:
x = 92
Step-by-step explanation:
The segment of measure 46 joins the midpoints of 2 sides of the triangle and is one half the measure of the third side, thus
x = 2 × 46 = 92
I need help. Look at picture
Choose 1 answer:
A. -4.63 x 10^13
B. -28.7
C. -1.65
D. -0.14
A survey of athletes at a high school is conducted, and the following facts are discovered: 68% of the athletes are football players, 26% are basketball players, and 23% of the athletes play both football and basketball. An athlete is chosen at random from the high school: what is the probability that the athlete is either a football player or a basketball player
Answer:
71% probability that the athlete is either a football player or a basketball player
Step-by-step explanation:
We solve this problem building the Venn's diagram of these probabilities.
I am going to say that:
A is the probability that an athlete is a football player.
B is the probability that an athlete is a basketball players.
We have that:
[tex]A = a + (A \cap B)[/tex]
In which a is the probability that an athlete plays football but not basketball and [tex]A \cap B[/tex] is the probability that an athlete plays both these sports.
By the same logic, we have that:
[tex]B = b + (A \cap B)[/tex]
23% of the athletes play both football and basketball.
This means that [tex]A \cap B = 0.23[/tex]
26% are basketball players
This means that [tex]B = 0.26[/tex]. So
[tex]B = b + (A \cap B)[/tex]
[tex]0.26 = b + 0.23[/tex]
[tex]b = 0.03[/tex]
68% of the athletes are football players
This means that [tex]A = 0.68[/tex]. So
[tex]A = a + (A \cap B)[/tex]
[tex]0.68 = a + 0.23[/tex]
[tex]a = 0.45[/tex]
What is the probability that the athlete is either a football player or a basketball player
[tex]A \cup B = a + b + (A \cap B)[/tex]
[tex]A \cup B = 0.45 + 0.03 + 0.23 = 0.71[/tex]
71% probability that the athlete is either a football player or a basketball player
Answer:
71%
Step-by-step explanation:
Applying Venn's diagram
probabilty that an athlete plays either football or basketball
P ( A ∪ B ) = a + b + ( A ∩ B ) equation 1
note:
P ( A ) = a + ( A ∩ B )
( A ∩ B ) = 23% = 0.23
a = P( A ) - 0.23 = 0.68 - 0.23 = 0.45
P ( B ) = b + ( A ∩ B )
b = P ( B ) - ( A ∩ B ) = 0.26 - 0.23 = 0.03
back to equation 1
P ( A ∪ B ) = 0.45 + 0.03 +( 0.23 )
= 0.48 + ( 0.23 ) = 0.71 = 71%
P( A ) = probability of football players
P ( B ) = probability of basketball players
a = probability of playing football but not basketball
b = probabilty of playing basketball but not football
NEED HELP ASAPPP !! find the y-intercept of the line of the graph.
Answer:
the Y intercept is (0,-2)
Step-by-step explanation:
It is the point on the graph which the line goes through the Y axis
Brainliest answer
Jack has 2 apples he gives one away to his sister how much apples does jack have left.
Answer:
1
Step-by-step explanation:
Answer:
1 apple
Step-by-step explanation:
2 - 1 = 1 <3
What is the standard deviation of the data? Round to the nearest whole number.
Answer:
Where's the data?
Step-by-step explanation:
The circumference of a circle is 31.4 miles. What is the circle's radius?
Answer:
About 5 miles or 4.9974 miles
Step-by-step explanation:
Formula: C = 2*π*r
31.4 miles = 2*π*r
Solve for r, the radius
r = 31.4 / 2*π = 4.9974 miles or about 5 miles
30 points and brainliest
Answer:A
Step-by-step explanation:
Because 4 is negative and would go left and 5 is positive so it would go up
What is the surface area of the square pyramid?
The surface area is ____ yd2.
Answer:
16
Step-by-step explanation:
Answer:
it is 16
Step-by-step explanation:
the height of both oblique and right prisms is ALWAYS
A) the perpendicular distance between the bases
B) the length of a lateral edge
C) longer than the altitude of the prism
D) drawn vertically
Answer:
Option A is correct.
The height of both oblique and right prisms is ALWAYS the perpendicular distance between the bases.
Step-by-step explanation:
Prisms are 3-D shapes that have two parallel faces (called bases) separated at some distance apart (the height of the prism) with the lateral face in between the two parallel bases.
For right prisms, the lateral face is a rectangle while it is a parallelogram for oblique prisms.
The height of a prism is the perpendicular distance between the two bases. In a right prism, the height is a lateral edge as this edge is equal to the perpendicular distance between the two bases.
In the case of the oblique prism, the height is the shortest line segment between the extended bases, the perpendicular distance between the two bases.
So, the height isn't always a length of a lateral edge, isn't always longer than the altitude of the prism and isn't always drawn vertically as the prism sometimes is pictured not resting on its bases, leading to the height drawn horizontally.
So, only option A is totally correct.
Hope this Helps!!!
Consider this study: A New York Times article published on April 24, 2007, reported the research of Dr. Giorgio Vallortigara, a neuroscientist at the University of Trieste, Italy, and his two colleagues. The researchers asked whether a dog wags its tail in a preferred direction in response to positive stimuli and in another direction in response to negative stimuli. To answer their question, they recruited 30 dogs that were family pets. Filming each dog from above, they allowed it to view (through a slat in its cage) three positive stimuli separately, in order of descending positivity: its owner, an unfamiliar human, and a cat. All the dogs responded by wagging their tails to the right. But when the dogs were presented with an unfamiliar, aggressive dog, a negative stimulus, all dogs wagged their tails to the left. Which of the following statements is the research hypothesis for this study?
a. A dog's tail will wag differently in response to positive stimuli and to negative stimuli.b. A dog's tail will wag more to the left in response to positive stimuli and more to the right in response to negative stimuli.c. A dog's tail will wag more to the right in response to positive stimuli and more to the left in response to negative stimuli.d. There will be no difference in a dog's tail wagging while viewing positive and negative stimuli.
Answer:
a. A dog's tail will wag differently in response to positive stimuli and to negative stimuli.
Step-by-step explanation:
A research hypothesis is a proposition that can be tested about the possible outcome of a study based on different stimuli.
A research hypothesis is a specific, clear, and testable proposition or predictive statement about the possible outcome of a scientific research study based on a particular property of a population, such as presumed differences between groups on a particular variable or relationships between variables.
Before a quantitative study takes place, it is important to state the research hypothesis because it is very important to the study.
There is usually an expectation or predicted outcome of the study because the research is determined by the hypothesis.
So it was already hypothesised that a dog would wag its tail in a preferred direction when it is faced with negative or positive stimuli. So the hypothesis was tested as different sets of dogs were placed in a cage and introduced to different stimuli.
From the observation of the researchers, all the dogs wagged their tails to the right when they saw a familiar face (positive stimuli) and wagged their tails to the left when they faced an aggressive dog (negative stimuli)
Un local de Santa Bárbara fue pintado por 4 personas emprendedoras que se unieron para montar un negocio de lácteos; Juan, Pedro, Carlos y Mario; Juan pintó 2/7 del local, Pedro pintó 5/14 y Carlos pintó 2/14; ¿qué fracción pintó Mario?
Answer:
The proportion of premises painted by Mario is [tex]\frac{3}{14}[/tex].
Step-by-step explanation:
The question is:
A local in Santa Bárbara was painted by 4 enterprising people who got together to start a dairy business; Juan, Pedro, Carlos and Mario; Juan painted 2/7 of the premises, Pedro painted 5/14 and Carlos painted 2/14; What fraction did Mario paint?
Solution:
Consider the proportion of the total premises painted is 1.
The four enterprising people who got together to start a dairy business are:
Juan (J), Pedro (P), Carlos (C) and Mario (M).
The proportion of premises painted by Juan is:
[tex]P(J)=\frac{2}{7}[/tex]
The proportion of premises painted by Pedro is:
[tex]P(P)=\frac{5}{14}[/tex]
The proportion of premises painted by Carlos is:
[tex]P(C)=\frac{2}{14}[/tex]
Compute the proportion of premises painted by Mario as follows:
P (M) = 1 - P (J) - P (P) - P (C)
[tex]=1-\frac{2}{7}-\frac{5}{14}-\frac{2}{14}\\=\frac{14-4-5-2}{14}\\=\frac{3}{14}[/tex]
Thus, the proportion of premises painted by Mario is [tex]\frac{3}{14}[/tex].
The oblique rectangular prism below has a length of 6 cm, a width of 8 cm, and a height of 7 cm. An oblique rectangular prism has a length of 6 centimeters, a width of 8 centimeters, and a height of 7 centimeters. What is the area of the base of the prism?
Answer:
48 cm²
Step-by-step explanation:
They are only asking for the area of the base of the prism, which is the length of the prism times the width of the prism.
B = area of base
l = length = 6 cm
w = width = 8 cm
B = l * w
B = 6 cm * 8 cm
B = 48 cm²
The area of the base of the prism is 48 cm²
Answer:
48
and
336
I just did it
Tablet: $439, 40% off find the discount
Answer:
439 x 0.4 = 175.6 so the discount is 175.6
Step-by-step explanation:
40% is equal to 0.4 and you just multiply. If you want to find the discount price just subtract the discount off.
Hope this helps can I have brainliest
Final answer:
The discount on the tablet is $175.60.
Explanation:
To calculate the discount on the tablet which is 40% off the original price of $439, we need to use the formula:
Discount = Original Price × Discount Rate
Therefore:
Discount = $439 × 40%
First, convert 40% into a decimal, which is 0.40:
Discount = $439 × 0.40
Do the multiplication to find the discount:
Discount = $175.60
So, the discount is $175.60, and the tablet would then cost $439 - $175.60 = $263.40 after applying the discount.